Management and Economics: Question of Development Goals - P. S. Tolkatchev (Управление, 2017)
The article discusses the relationship of economic management with the economic basis. The thesis is substantiated that effective economic management depends on economic ideal, to which society will strive to achieve. The world surrounding a person constantly retains its essential fundamental properties. And in this way it is perfect. Man spiritually assumes himself above nature. Potentially, he sees himself as a master of the natural world. However, acting in nature as an independent free force, he constantly reveals his imperfect. Because of his limited knowledge of the infinitely complex nature, everything that a person creates is imperfect. The path to perfection is the natural goal of man’s life on earth. However, on this common path, all nations and their large groups – civilizations – are moving along different roads. And in modern conditions, these differences have reached a dangerous feature – more and more the confrontation of civilizations is emerging. The historical feature of the Russian economic worldview is the absolute priority of moral ideals. Its deep economic ideals are not aggressive in relation to other countries and peoples. These ideals are in finding and multiplying of good. Therefore, potentially, Russia can counteract the negative scenario of the development of civilizational conflicts.